ChemInform Abstract: Carboxyl Activation via Silylthioesterification: One‐Pot, Two‐Step Amidation of Carboxylic Acids Catalyzed by Non‐Metal Ammonium Salts. Issue 9 (February 2016) - Lamar, Angus A.; Liebeskind, Lanny S.
Abstract: In situ generated o‐silylthionoesters react with amines to afford amides in an operationally simple one‐pot procedure without removal of water.